Effects of switching from dipeptidyl peptidase 4 inhibitors to oral semaglutide on oxidative stress and glycemic variability in patients with type 2 diabetes: an open-label, prospective, randomized, multicenter, parallel-group comparison study - Makoto Ohara; Hiroki Yokoyama; Hiroaki Seino; Tomoki Fujikawa; Yo Kohata; Noriyuki Takahashi; Shunichiro Irie; Michishige Terasaki; Yusaku Mori; Tomoyasu Fukui; Sho-ichi Yamagishi (Diabetology & Metabolic Syndrome)
Abstract Background To compare the effects of switching from dipeptidyl peptidase 4 (DPP-4) inhibitors to oral semaglutide on oxidative stress and glucose variability assessed by continuous glucose monitoring in patients with type 2 diabetes mellitus (T2DM). Methods This was an open-label, prospective, randomized, multicenter, parallel-group comparison study conducted over 24 weeks. Patients with T2DM who had been taking regular doses of DPP-4 inhibitors for at least 12 weeks were enrolled. They were randomly assigned to either continue on DPP-4 inhibitors (DPP-4 inhibitor group) or switch to oral semaglutide at 3 mg/day, with a dose increase to 7 mg/day after 4 weeks (semaglutide group). The primary endpoint was the change in the diacron-reactive oxygen metabolites test, an oxidative stress marker. Secondary endpoints included changes in glucose variability assessed using continuous glucose monitoring, metabolic indices, physical assessments, and Diabetes Treatment Satisfaction Questionnaire scores. Results Fifty-eight patients with T2DM were randomized to the semaglutide group (n = 30) and the DPP-4 inhibitor group (n = 28). Six patients in the semaglutide group and one patient in the DPP-4 inhibitor group dropped out during the study. Ultimately, data from 24 patients in the semaglutide group and 27 patients in the DPP-4 inhibitor group were included for analysis. Switching to oral semaglutide therapy for 24 weeks significantly reduced oxidative stress, glucose variability, and hemoglobin A1c levels compared to continuous treatment with DPP-4 inhibitors. However, there was no significant difference in Diabetes Treatment Satisfaction Questionnaire scores between the two groups. (II) Conclusions Our study demonstrated that switching to oral semaglutide therapy from DPP-4 inhibitors significantly improved oxidative stress and glycemic parameters, including glucose variability, in patients with T2DM. Trial registration: jRCT1031210620.